1993
DOI: 10.1111/j.1600-0897.1993.tb00597.x
|View full text |Cite
|
Sign up to set email alerts
|

No Detection of Interferon‐γ Activity During Early Pregnancy in the Mouse

Abstract: We conclude that in this rodent species IFN-gamma is most probably not involved in early maternal-fetal interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
(10 reference statements)
1
2
0
Order By: Relevance
“…In mice, knock-out experiments showed that IFN-γ is not required for normal embryonic development or the generation of a specific immune response [38]. These findings confirmed previous results showing that no IFN (type I or type II) can be detected during early pregnancy in mice [44].…”
Section: Possible Role In Conceptus Implantationsupporting
confidence: 81%
See 1 more Smart Citation
“…In mice, knock-out experiments showed that IFN-γ is not required for normal embryonic development or the generation of a specific immune response [38]. These findings confirmed previous results showing that no IFN (type I or type II) can be detected during early pregnancy in mice [44].…”
Section: Possible Role In Conceptus Implantationsupporting
confidence: 81%
“…Other evidence that IFN-γ is secreted by the human villous syncytiotrophoblast and extravillous trophoblast in decidua during the first trimester of pregnancy was found, followed by a significant decline in secretion up to term pregnancy, where only a weak signal of IFN-γ was detected in extravillous trophoblast in the decidua [63]. In mice, no IFNs or IFN-like activity was detected during early pregnancy [44].…”
Section: Embryonic Interferons In Mammalsmentioning
confidence: 98%
“…It is induced in the early decidua and remains cytoplasmic in the trophectodermal lineages throughout placental development [17]. By midpregnancy, IFNG is detected in trophoblast giant cells [18,19]. IFNG receptor 1 (IFNGR1) and IFNGR2 are found on mouse oocytes and preimplantation embryos.…”
Section: Introductionmentioning
confidence: 99%